PSYCHOLOGICAL CHARACTERISTICS OF "EXIT FROM WAR" - Оніщенко, Н.; Тімченко, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The psychological and social characteristics of the return to a peaceful life for Soviet officers and soldiers have been considered. There are veterans of the Second World War and the Afghan War and members of local military conflicts that took place on the territory of post-Soviet countries. Keywords: war, soldier, a member of local military conflicts, psychogenic disease.